Friendship groups and physical activity: qualitative findings on how physical activity is initiated and maintained among 10-11 year old children - Page Angie S; Cartwright Kim; Fox Kenneth R; Brockman Rowan; Jago Russell; Thompson Janice L (BMC, 2009)
Abstract Background Many youth physical activity interventions have minimal effect. To design better interventions we need to understand more about the factors that influence youth activity. Application of self-determination theory to youth physical activity, particularly the relatedness and competence, might suggest that friends and friendship groups influence the initiation and maintenance of youth physical activity. In this study we examined this issue. Methods Seventeen focus groups were conducted with 113, 10-11 year old children, from 11 primary schools in Bristol, UK. Focus groups examined: 1) the nature of children's friendship groups; 2) associations between physical activity and social group status; and 3) how friendship groups affect the initiation and maintenance of physical activity. All focus groups were audio-taped and transcribed verbatim. Data were analyzed using content analysis. Results Participants reported that there were three different types of friendship groups; School friends; Neighborhood friends; and Other Friends who were friends from organized activities or children of their parents' friends. Participants had multiple groups of friends and engaged in different activities with the different groups. Possessing several groups of friends was desirable as it kept the friendships fresh and interesting. Physical activity was perceived as a positive attribute and linked to social status among boys. Among girls the association between physical activity ability and social status was more complex, appearing to differ by the norms of the group to which participants belonged. Some participants reported that low activity ability could be perceived as desirable in some social groups. Participants reported that friends provide support to initiate physical activity via co-participation (i.e. engaging in activity together); modeling of being active; and providing verbal support to engage in activity. Enjoyment was the most important factor in maintaining activity participation with participating in activity with friends a key factor influencing enjoyment. Conclusion Friendship groups affect both the initiation and maintenance of youth physical activity. Children belong to several groups and engage in different activities with different groups. Simple strategies that aim to promote physical activity via the different friendship groups could be an effective means of promoting increased physical activity in young people.